UNRAVELLING ATRIAL FIBRILLATION AETIOLOGY AND ANTICOAGULATION TRENDS IN STROKE. WHERE DO WE STAND? A STUDY FROM NORTHERN PAKISTAN - Farhat Naz; Saqib Malik; Khazima Asif; Mehreen Mahsood; Sadia Rehman; Najma Rehman (Journal of Ayub Medical College Abbottabad, 2024)
Background: Atrial Fibrillation is a heart arrhythmia causing stroke and associated with many modifiable risk factors. A number of strokes can be prevented by identifying these risk factors and adopting primary prevention and anticoagulation. Methods: This Cross-Sectional observational study on 160 stroke patients; identified frequency and risk factors of Atrial Fibrillation and their prior anticoagulation status. Correlation of risk factors associated with Atrial Fibrillation in stroke was done through Chi Square test. Results: Among 160 patients, 72 (45%) were males and 88 (55%) females. Mean age was 64.29±13.44SD with range of 31-92 years. Among patients, 113 (70.6%) had ischemic stroke, and 32(20%) had Atrial Fibrillation. Among risk factors, 136(85%) had hypertension, 37(23.1%) had diabetes, 52(32.5%) had ischemic heart disease, 27(16.9%) had valvular heart disease, 9 (5.6%) had hyperthyroidism, 37(23.1%) had hyperlipidemia, 17(10.6%) had chronic respiratory disease, 19 (11.9%) were smokers, 61(38.1%) had family history of stroke, 12(7.5%) were obese. Only 8 of 32 with AF (25%) had prior anticoagulation. Correlation analysis of risk factors show ischemic heart disease (p=.000285), rheumatic heart disease (p=.000061), hyperlipidemia (p=.0004), chronic respiratory disease (p=.003175) and smoking (p=.00148) as significantly associated with Atrial Fibrillation. Conclusion: Ischemic heart disease, hyperlipidemia, smoking and respiratory disease are significant risk factors for stroke in non-valvular atrial fibrillation. All these factors are modifiable so primary prevention and prophylactic anticoagulation should be emphasized.